The place of history subjects in the social studies textbooks. - DOLMAZ, Mustafa; METİN, Özge (Turkish History Education Journal (TUHED), 2021)
The history and social studies that discuss the social life in all aspects including the political, economic, social and cultural dimensions teaches the history to individuals as a solider of the curriculum gathered at a common point which adapts these individuals to the existing period and society and prepares them for the future. While the important part of the social studies content comes from history, its mission is to complete some of the tasks undertaken by history. These tasks including providing the historical content and skills and values related to the historical subjects to the students. This study aims to determine how intensely history subjects are included in the social studies textbooks prepared in our country with an interdisciplinary approach, how much of the lesson's target acquisitions are related to history, and what skills and values are desired to be acquired by students in historical subjects. The document analysis method, which is one of the qualitative research methods, was used in this study. The data source of the study consists of social studies textbooks used at the 4th, 5th, 6th, and 7th-grade levels. The "Book Evaluation Form" prepared by the researchers was used as the data collection tool. The obtained data were analyzed by the descriptive analysis method. As a result of the research, it was observed that approximately one-third of the subjects and acquisitions in the social studies course textbooks were historical directly or indirectly and that historical subjects were designed to support the development of a total of 17 skills, including, critical thinking, innovative thinking, high-level thinking skills, etc. Also, history subjects have content to support all other values in the curriculum except savings value. In the suggestions section, suggestions were made to increase the weekly course hours of social studies lesson and to include values such as tolerance, hospitality, altruism, humility, bravery, and courage, which are identified with Turkish history, into the program concerning history issues to carry out practical activities based on the targeted skills.